Tajemnica korespondencji. O "Cudzych listach" Macieja J. Drygasa - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2012)
The Secret of Correspondence. On Maciej J. Drygas’s Documentary Film „Someone’s else letters” (2010) Maciej J. Drygas teaches film direction at Film School in Łódź. His lavishly illustrated recent work “Someone’s else letters” is one of the best Polish editing documentaries ever made. The product of extensive research provided by the author in many archives is sure to provoke much debate and discussion about lack of freedom, breaking law by the state secret institutions, crucial importance of human rights and misery of everyday life conditions in Poland 1944-1989. In so doing Drygas greatly enlarges our knowledge and the scope of any understanding of this period. Marek Hendrykowski’s study is the first complete presentation ever published, covering every aspect of this excellent film, expressing its significance and including detailed analysis of its poetics.